De la description des circulations à la territorialisation des réseaux : 35 ans de géographie des transports dans « Hommes et Terres du Nord ». - Philippe Ménerault; Alain Barré (Territoire en Mouvement)
This paper deals with the articles involving transport geography that have been published in the review « Hommes et Terres du Nord » since 1970. In a chronological approach, it shows the evolution of the themes and the transition form a descriptive geography to a geography more influenced by planning perspectives.